A study on the impact of chief executive officer / managing director's selection, succession and compensation on the firm's performance - Leow, Chu Meng (2015)
This study attempts to explore a set of research issues relating firm's performance to CEO selection, succession & compensation in the Singapore context. The study offers a model of these issues from a combined agency and organisational perspective. Five hypothesis formulated were tested using data from survey responses from 53 CEOs of the firms listed on SES mainboard and SESDAQ. Financial data from the audited financial reports of the relevant companies were collected to determine firm's performance Our findings revealed that firms with CEO selected from within generally have better performance than others. This is consistent with our argument that the board of directors would have the advantage of observing the characteristics of an insider, thus reducing the chances of adverse selection. It is also found that firms with a clear succession plan for CEO outperform those without it. This is because succession plans are generally viewed as a favourable signals about the quality and development of high quality top management. The use of adverse selection to explain the distinction between an insider versus· an outsider offers a new theoretical viewpoint that could be further explored in future researches. In addition, a logical and important extension of this research would be to examine succession planning systems in greater detail to assess whether the signals mentioned are accurate and how to make use of such favourable signals. On the compensation aspect, CEO's satisfaction with his compensation scheme is found to be directly linked to firm's performance. Hence, compensation scheme should be designed to suit the needs of the CEO such that he/she is satisfied and feels motivated. The CEO's perception of the connection between his wealth and the firm's wealth is also shown to have significant effects on firm's performance. This finding adds value to the literature on CEO compensation as it reveals another factor which affects CEO's satisfaction towards his compensation scheme - CEO's compensation relative to his total wealth. CEO's perception of the connection between his reputation with the wealth of the company, however, does not have any significant effect on firm performance. This result is rather unexpected as CEOs generally do perceive a connection between their reputation and the firm performance. This calls for future research to identify the possible non-financial factors which intervened in our results and remained unaccounted for in our study.